PERANAN PENGENDALIAN INTERNAL PERSEDIAAN BARANG DAGANG DALAM MENUNJANG EFEKTIVITAS PENGELOLAAN PADA STUDI KASUS: PT. SAMSUNG ELECTRONICS INDONESIA CABANG MANADO - Lakoy, Prilly; Poputra, Agus Toni (ACCOUNTABILITY, 2016)
This study aimed to analyze the role of internal control in supporting goods inventory for effectiveness of goods inventory at PT. Samsung Electronics Indonesia Manado branch located at Jl. Toar No. 1, Manado North Sulawesi in the electronics division. This type of research used descriptive analysis by observing the understanding of internal control procedures through tests of controls, then documenting the company's internal control information using a process flow chart, goods reception and delivery of goods as well as elements of internal control are applied. The data used in this study are primary data and secondary data. primary data obtained from interviews and direct observation and secondary data obtained through the literature related to control testing, company documentation, the data types available in warehouse stock inventory, shipping and receiving process flow of goods and other data related to this study. The results showed PT. Samsung Electronics Indonesia in Manado branch has been quite effective in performing internal control both in its application through the five elements, namely elements of the control environment, risk assessment, control activities, information and communication and monitoring.